Flexural and Microstructural Behavior of Reinforced Concrete Beams Using River and Beach Sand Aggregates - Muhammad Irwansyah; Dwi Maharani (Nucleus Journal, 2026)
This study investigates the influence of river sand and beach sand as fine aggregates on the flexural behavior, mechanical properties, and microstructural characteristics of reinforced concrete beams. The increasing scarcity of river sand and environmental concerns associated with excessive mining have encouraged the exploration of alternative fine aggregates such as beach sand. However, the high chloride content and different particle characteristics of beach sand may affect concrete performance and durability. In this research, reinforced concrete beams were experimentally evaluated using two types of fine aggregates and two reinforcement configurations, namely plain and deformed reinforcement bars. The experimental program included compressive strength testing, flexural testing under two-point loading, water absorption testing, porosity analysis, and microstructural characterization using Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD). The results showed that concrete containing river sand exhibited higher compressive strength and lower porosity compared to concrete containing beach sand. The average compressive strength of river sand concrete reached 24.85 MPa, while beach sand concrete achieved 17.69 MPa. Flexural testing indicated that beams reinforced with deformed bars demonstrated better performance than beams with plain reinforcement. SEM observations revealed that beach sand concrete possessed a more porous microstructure and weaker interfacial transition zones, while XRD analysis confirmed that the primary hydration products remained similar for both concrete types. Overall, beach sand has potential as an alternative fine aggregate, although additional treatment and quality control are required to improve its mechanical and durability performance.